Determining the feasibility of linked claims and vaccination data for a COVID-19 vaccine pharmacoepidemiological study in Germany—RiCO feasibility study protocol - Peter Ihle; Brigitte Keller-Stanislawski; Ingo Meyer; Nina Timmesfeld; Robin Denz; Katherina Meiszl; Katrin Scholz; Doris Oberle; Ursula Drechsel-Bäuerle; Hans H Diebner (BMJ Open)
Introduction In Germany, there has been no population-level pharmacoepidemiological study on the safety of the COVID-19 vaccines. One factor preventing such a study so far relates to challenges combining the different relevant data bodies on vaccination with suitable outcome data, specifically statutory health insurance claims data. Individual identifiers used across these data bodies are of unknown quality and reliability for data linkage.Methods and analysis As part of a larger pharmacovigilance study on the COVID-19 vaccines, called RiCO (German ‘Risikoevaluation der COVID-19-Impfstoffe’, Englisch ‘Risk assessment of COVID-19 vaccines’), a feasibility study is being conducted to determine the overall confidence level with which existing data can be analysed in relation to the safety of the COVID-19 vaccine. This RiCO feasibility study will establish a data flow combining claims data and vaccination data for a subsample of the total German population, describe data quality for each dataset from the various sources, estimate the proportion of the different linkage errors and will develop various approaches for linking the data in addition to the simple form of linkage using a common identifier in order to reduce possible linkage errors. These last three points are the core objective of the feasibility study. A secondary objective is to test the viability of the required data flow involving multiple stakeholders from different parts of the healthcare system.Ethics and dissemination Results will be published and used to plan the actual pharmacovigilance study on the COVID-19 vaccines for Germany, as well as future research on the role of COVID-19 vaccines as risk or protective factors for long-term COVID-19 effects. In accordance with national legal requirements, permission to use of the statutory health insurance claims data was requested and granted by the national regulatory authority for statutory health insurances. The vaccination data will be used in accordance with the requirements of the national regulation on COVID-19 vaccinations. Ethical approval was not required for this secondary data study and was therefore not sought. The results of the feasibility study will be published in a suitable, peer-reviewed scientific journal. Results will also be presented to stakeholders from German statutory health insurances and government organisations.